Transcription factor 25 modulates gametocytogenesis and ribosome biogenesis in the malaria parasite Plasmodium falciparum - Wu, Jing; Zhang, Zuping; Ngim, Chandara; Yang, Wenyu; Li, Peiyi; Wang, Fei; Ye, Jingru; Li, Bo; Tian, Bin; Zhang, Qingfeng; Shang, Xiaomin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionPlasmodium falciparum, the causative agent of severe malaria, predominantly reproduces through asexual stages within human red blood cells, with a small subset differentiating into transmissible gametocytes. TCF25 is recognized in other eukaryotes as a protein with dual roles: a transcriptional regulator and a key component of the Ribosome-associated Quality Control (RQC) complex. Nevertheless, the precise biological function of TCF25 in Plasmodium spp. remains inadequately elucidated.MethodsTo investigate the function of TCF25, we created a tcf25 knockout (tcf25_ko) parasite strain and conducted comparative transcriptomic analysis during the ring and schizont stages. Gametocyte induction experiments were performed to investigate the impact of tcf25 deletion on gametocyte development. Chromatin immunoprecipitation sequencing (ChIP-seq) was utilized to delineate the genome-wide binding profiles in schizont-stage parasites. Additionally, RT–qPCR was used to quantify changes in rRNA expression levels after tcf25 knockout.ResultsTranscriptomic analysis of tcf25_ko parasites indicated substantial dysregulation, with 168 genes downregulated and 24 genes upregulated during the ring stage, and 53 genes downregulated and 4 genes upregulated during the schizont stage. ChIP-seq analysis identified 44 high-confidence TCF25-binding target genes, which notably included the rDNA. Furthermore, TCF25 deficiency resulted in upregulated rRNA expression, particularly affecting 28S rRNA, a core component of the 60S ribosomal subunit.DiscussionThis study identifies TCF25 as a key regulator of various biological processes in P. falciparum. It is shown that TCF25 plays a crucial role in gametocytogenesis by influencing the ap2-g pathway. Additionally, a novel function of TCF25 in ribosomal biogenesis is uncovered, wherein it directly controls A-type rRNAs expression and ribosomal subunit homeostasis. These discoveries offer fresh perspectives on the molecular mechanisms that oversee transmission and ribosome biogenesis in malaria parasites.